Polysaccharide of L. casei SB27 reduced colon cancer cell prognosis through mitochondrial damage by up-regulation of HINT2. Issue 4 (December 2022) - Di, Wei; Li, Xin; Yang, Qiaoyi
Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors of the digestive system worldwide. This study aimed to explore the effects of Polysaccharide of L. casei SB27 in colon cancer and its possible mechanisms. Colon cancer was induced by giving dextran sulfate sodium and Azoxymethane. HCT-116 cells were used in to in vitro model in this experiment. Polysaccharide of L. casei SB27 reduced colon cancer in DSS + AOM-induced mice. Polysaccharide of L. casei SB27 reduced colon cancer prognosis in vitro model. Polysaccharide of L. casei SB27 reduced Short-chain fatty acids by Bacillus coli. Polysaccharide of L. casei SB27 promoted A mitochondrial damage by Calcium ion entry. Polysaccharide of L. casei SB27 induced HINT2/MCU signaling pathway. IP showed that HINT2 protein interlinked MCU protein. Polysaccharide of L. casei SB27 suppressed HINT2 Ubiquitination. The regulation of HINT2 affected the effects of L. casei SB27 Polysaccharide on colon cancer Prognosis and A mitochondrial damage by Calcium ion entry in vitro model. In conclusion, the present report demonstrated that Polysaccharide of L. casei SB27 reduced colon cancer cell Prognosis through A mitochondrial damage by up-regulation of HINT2. Polysaccharide of L. casei SB2 7 might be used for colon cancer treatment and could be helpful for personalized treatment.